2012
DOI: 10.1590/s0103-84782012000800027
|View full text |Cite
|
Sign up to set email alerts
|

Enzimas exógenas em dietas de frangos de corte: desempenho

Abstract: RESUMO O experimento foi conduzido para avaliar a eficiência de enzimas exógenas em dietas sobre o desempenho de frangos de corte. Um total de 1440 pintos de corte machos (Cobb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
2
6
1
6
Order By: Relevance
“…These results are consistent with the findings of Barbosa et al (2012), who observed that the supplementation of enzyme blends to diets with reduced mineral and energy levels promoted similar feed intake and weight gain that broilers fed a standard diet during the starter phase. Brito et al (2006), using an enzyme complex containing amylase, protease, and xylanase, observed increased weight gain and improved feed conversion ratio in broilers between 1 to 21 days of age, as opposed to the findings of the present experiment.…”
Section: Enzyme Supplementation Of Broiler Feeds With Reduced Mineralsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the findings of Barbosa et al (2012), who observed that the supplementation of enzyme blends to diets with reduced mineral and energy levels promoted similar feed intake and weight gain that broilers fed a standard diet during the starter phase. Brito et al (2006), using an enzyme complex containing amylase, protease, and xylanase, observed increased weight gain and improved feed conversion ratio in broilers between 1 to 21 days of age, as opposed to the findings of the present experiment.…”
Section: Enzyme Supplementation Of Broiler Feeds With Reduced Mineralsupporting
confidence: 92%
“…On the other hand, enzyme complex is derived from the fermentation with a single microorganism that synthesizes several enzymes. Barbosa et al (2012), studying the efficacy of enzymes in broiler diets, found that the addition of phytase, amylase, xylanase, and protease in diets with reduced metabolizable energy, calcium, and phosphorus content, promoted similar feed intake and weight gain than a diet with adequate nutrient levels. According to the authors, enzyme blends can be added to diets with reduced nutrient levels aiming to maintain broiler growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the use of the additives indicate, as suggested by Barbosa et al (2012) and Wang et al (2016), that the use of an emulsifier and lipase have a more evident beneficial effect on the performance of broiler chickens in diets with a reduced level of metabolisable energy than diets with energy and nutritional levels attended (on-top concept), thus improving the energy efficiency of the diet (higher net energy) and consequently improving the characteristics of performance of the broilers at the end of the growing cycle.…”
Section: Concomitantsupporting
confidence: 56%
“…O nível de P da dieta deve atender não só as exigências das aves para a manutenção do desempenho, mas também deve fornecer quantidade de P suficiente para contribuir para a adequada mineralização óssea (Santos et al, 2008;Assuena et al, 2009;Barbosa et al, 2012). Os PN que resultaram no maior consumo de ração e ganho de peso dos frangos, no período de 8 a 42 dias, e no maior teor de cinzas nas tíbias, aos 42 dias de idade, foram os PN 1, 2 e 5.…”
Section: Pnunclassified